Between-tree variations in leaf Î´ 13 C of Quercus pubescens and Quercus ilex among Mediterranean habitats with different water availability (Oecologia, 1997)
In this study, sun leaf carbon isotope compo- sition (d 13 C) of two co-occurring woody Mediterranean species (Quercus pubescens Willd., a deciduous oak, and Q. ilex L., an evergreen one) was investigated on four sites with dierent water availability. The total range of d 13 C values was 4.4 and 3.1& for Q. pubescens and Q. ilex respectively. The intra-site variability was about 3&. Total mean per species was equal. There were sig- ni®cant dierences among sites, but at each site means of d 13 C were not signi®cantly dierent between species. A simple physiological model predicts no dierence in in- trinsic water-use eciency (WUEi ) between evergreen and deciduous oaks. The relationship between site means of d 13 C and water parameters suggests that there is a leaf functional adjustment with respect to available water resource. No correlation was found between d 13 C and the contents of any mass-based biochemical cons- tituent. Nevertheless there was a signi®cant correlation between d 13 C and leaf mass per area of Q. ilex. For both species, there is also a positive correlation between leaf d 13 C and individual crown area, i.e. a structural char- acteristic at tree level. Causal relations between d 13 C and plant-environment interactions are discussed.